Investigating the current risk management process practice in Malaysian landscape planning projects - S. Muthuveeran, Adam Aruldewan; Mohd Tahir, Osman; Hassan, Mohd Azren; Yin, Izuandi (Malaysian Institute of Planners, 2022)
The Malaysian landscape planning projects are dynamic, subjective, and fasttracked, causing multiple risks. Hence, risk management practice is needed to manage risks. However, the risk management process is not managed comprehensively despite the considerable capability of project practitioners to predict, analyse, and treat project risks, causing the project to underperform. This study has investigated the current risk management process in Malaysian landscape planning projects. Data were gathered through semi-structured interviews with twenty-four landscape architect practitioners from Klang Valley. The information from the interviews was analysed utilising the content and thematic analysis method. The six steps of the risk management process were not managed following the suggested methodology, whereby the procedure was carried out in an ad hoc, unstructured, and incomplete manner. This action has caused extensive risk impact which affected project performances. This finding will teach project practitioners to evaluate their current practice and recommend the adoption of formal risk management in landscape planning projects.